A prognostic human brain network for diffuse midline glioma - Jai Sidpra; Valentina Lind; Alexander L. Cohen; Frederic L. W. V. J. Schaper; Thomas J. Stone; Yura Grabovska; Asthik Biswas; Sniya Sudhakar; Francisco Sepulveda; Bruno S. Peres; Greta Veronese; Cristina Alemán-Charlet; et al. (Nature, 2026)
Abstract Diffuse midline gliomas (DMGs) are near-universally lethal tumours of the childhood central nervous system 1,2 . In animal models, DMGs form brain-wide integrated networks through neuron-to-glioma synapses 3–6 and glioma-to-glioma gap junctional coupling 3 . This extensive connectivity robustly promotes the growth and invasion of DMG 3–9 and other glial malignancies 10–12 through paracrine mechanisms and direct neuron-to-glioma synapses. However, the organization and clinical implications of these connections in the living human brain remain to be elucidated. Here, we develop tumour network mapping to compute the brain-wide connectivity profile of DMG, defining a conserved brain network across pontine and thalamic DMG associated with patient short-term survival (DMG network). Tumour functional connectivity with the DMG network was independently predictive of patient overall survival across two external validation cohorts. Tumour growth mapped to DMG network-specific trajectories and peak in-network neurometabolic changes across development spatiotemporally aligned with the peak age incidence of DMG. Analyses of single-nucleus RNA sequencing data confirmed diverse synaptic gene enrichment in high-connectivity DMG. Strikingly, incidental surgical resection of high-connectivity thalamic DMG tissue conferred a significant survival advantage. Collectively, these data define a conserved and prognostically important brain network in children with DMG, consistent with the hypothesis that DMGs exploit otherwise healthy brain circuits to promote tumour growth.